The efficient measurement of individual differences in meaning motivation: The need for sense-making short form - Cantarero, Katarzyna; van Tilburg, Wijnand A. P.; Gasiorowska, Agata; Igou, Eric R. (Frontiers in Psychology, 2022)
People differ in the extent to which they express a need for sense-making (NSM), and these individual differences are important to understand in light of meaning-making processes. To quantify this important variable, we originally proposed a need for sense-making scale (Cantarero et al., 2021). We now propose a refined, similarly reliable short version of the scale (NSM-SF). The 7-item NSM-SF was validated across a series of four studies (combined N = 1,243). NSM-SF showed psychometric properties and correlations consistent with its longer forerunner. Additionally, results indicated that the need for sense-making was moderately positively related to the satisfaction of basic psychological needs (autonomy, relatedness and competence), and it related negatively to the frustration of these needs. The research offers a useful, brief tool for assessing the NSM construct and broadens our understanding of basic psychological motivations.